Washington, D.C., architecture collection
Correspondence, clippings, and printed matter, concerning an architecture and sculpture competition for erection of public buildings and memorials in the District of Columbia and elsewhere.
Collection material in English.
Keywords: Architecture -- Washington (D.C.); Memorials -- Washington (D.C.); Public buildings -- Washington (D.C.); Sculpture -- Washington (D.C.)